TEACHING MODELS FOR CHILDREN WITH MODERATE INTELLECTUAL DISABILITIES DURING COVID-19 PANDEMIC - Asep Supena; Uswatun Hasanah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This study aims to analyze learning models appropriate for children with moderate intellectual disabilities during the COVID-19 pandemic because all learning in schools turn into distance learning. This period is very crucial, especially for children with moderate learning disability in learning. This research used a qualitative method with a case study. Data collection was done through in-depth interviews and observations. The subjects were two special education teachers, a homeroom teacher, and two parents of children with moderate intellectual disabilities. Thematic analysis was used to interpret the research findings. In this study, the answers of parents and teachers as respondents were evaluated. The results showed a suitable learning model to use during this pandemic was a project-based individual learning model. Teachers could provide a simple project containing soft skill and hard skills for children with intellectual disabilities controlled under their parents' supervision. The focus of learning was not on achieving cognitive abilities as in general, but on how they could be skilled and independent in carrying out activities. The findings of this research could provide teachers and parents with solutions in guiding learning activities for children with moderate intellectual disabilities, especially during the COVID-19 pandemic.Abstrak:Penelitian ini bertujuan untuk menganalisis model pembelajaran yang sesuai untuk anak tunagrahita sedang pada saat pandemi COVID-19 karena semua pembelajaran di sekolah berubah menjadi pembelajaran jarak jauh. Periode ini sangat krusial, terutama bagi anak-anak dengan ketidakmampuan belajar sedang dalam belajar. Penelitian ini menggunakan metode kualitatif dengan studi kasus. Pengumpulan data dilakukan melalui wawancara mendalam dan observasi. Subjek penelitian ini adalah dua orang guru pendidikan luar biasa, seorang wali kelas, dan dua orang tua anak tunagrahita sedang. Analisis tematik digunakan untuk menafsirkan temuan penelitian. Dalam penelitian ini, jawaban orang tua dan guru sebagai responden dievaluasi. Hasil penelitian menunjukkan model pembelajaran yang sesuai untuk digunakan selama pandemi ini adalah model pembelajaran individu berbasis proyek. Guru dapat memberikan proyek sederhana yang berisi soft skill dan hard skill untuk anak tunagrahita yang dikendalikan di bawah pengawasan orang tua. Fokus pembelajaran bukan pada pencapaian kemampuan kognitif seperti pada umumnya, tetapi pada bagaimana mereka bisa terampil dan mandiri dalam melakukan aktivitas. Temuan penelitian ini dapat memberikan solusi kepada guru dan orang tua dalam memandu kegiatan pembelajaran bagi anak tunagrahita sedang, khususnya pada saat pandemi COVID-19.